Optimization of drilling processes in panel furniture manufacturing: A case study - Guokun Wang; Xiaoli Li; Xianqing Xiong; Siqun Wang (PLoS ONE, 2025)
The drilling process is a crucial component in the production of panel furniture enterprises; simultaneously, it is also the most complex process. And the furniture enterprise’s transition to intelligent manufacturing lacks effective process optimization. Therefore, this study focuses on optimizing the drilling process in panel furniture. Initially, an analysis of cabinet structures was conducted, followed by data collection on drilling patterns. Based on this data and insights from hole distribution patterns, a novel COING (Coordinate Information Grid) data analysis method was proposed. Subsequently, the application of this method at the Company W, combined with the ARM (Association Rule Mining) method, revealed inconsistencies in drilling process parameters. After proposing and validating solutions in the Company W’s workshop, the findings demonstrated a 14.0% reduction in drilling occurrences and a 3.87% enhancement in drilling efficiency. This study demonstrates the optimization of drilling processes in panel furniture manufacturing.